A Facile Microwave-Assisted Hydrothermal (MAH) Method of CdWO4/CdMoO4 Heterostructures and Their Photocatalytic Properties - Nivaldo F. Andrade Neto; Onecima B. M. Ramalho; Marcio D. Teodoro; Mauricio R. D. Bomio; Fabiana V. Motta (Ceramics)
In this study, CdWO4/CdMoO4 powders’ heterostructures were synthesized using the microwave-assisted hydrothermal method, characterized, and evaluated for their photocatalytic properties. The samples were analyzed using X-ray diffraction (XRD), Raman and ultraviolet-visible (UV-Vis) spectroscopy, field-emission scanning electron microscopy (FESEM), and photoluminescence (PL). The photocatalytic performance was assessed using methylene blue as a model pollutant. XRD patterns and Raman spectra confirmed the formation of heterostructures containing the Wolframite phase of CdWO4 and the Scheelite phase of CdMoO4. FESEM micrographs revealed that the CdWO4 phase exhibits a plate-like morphology, while the CdMoO4 phase consists of irregular nanoparticles. Photocatalytic tests demonstrated that the 20Mo sample exhibited the best performance, degrading 96% of the dye after 2 h of reaction. The findings of this study indicate that CdWO4/CdMoO4 heterostructures hold significant potential for photocatalytic applications in the degradation of cationic dyes.